The Effect of Leadership Style and Work Culture on Employee Performance through Job Satisfaction as an Intervening Variable (Case Study at PT. Jaya Makmur Electrindo) - Priscillia Christe Dewi Portier; I Ketut Mastika; Yuslinda Dwi Handini (Universitas Muhammadiyah Jember Press, 2026)
Optimal individual performance enhances productivity and reflects the effectiveness of human resource management. Job satisfaction is an important driver of performance and is shaped by leadership style and organizational culture. Effective leadership provides direction, motivation, and support, while a supportive culture fosters a positive and productive work environment. Since 2010, PT Jaya Makmur Electrindo (PT JME) has entered a new leadership era that introduced organizational restructuring and continuous cultural transformation. This study analyzes the effects of leadership style and organizational culture on employee performance, with job satisfaction as an intervening variable. A quantitative approach was applied using primary data collected through questionnaires and interviews, supported by secondary data. The sample comprised 104 employees of PT Jaya Makmur Electrindo. The findings show that leadership style has a direct positive effect on employee performance and a stronger indirect effect through job satisfaction. Organizational culture does not directly influence performance; however, it positively affects job satisfaction, which subsequently enhances employee performance.